2014
DOI: 10.1051/0004-6361/201321624
|View full text |Cite
|
Sign up to set email alerts
|

The Mice at play in the CALIFA survey

Abstract: We present optical integral field spectroscopy (IFS) observations of the Mice, a major merger between two massive ( 10 11 M ) gas-rich spirals NGC 4676A and B, observed between first passage and final coalescence. The spectra provide stellar and gas kinematics, ionised gas properties, and stellar population diagnostics, over the full optical extent of both galaxies with ∼1.6 kpc spatial resolution. The Mice galaxies provide a perfect case study that highlights the importance of IFS data for improving our under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 132 publications
7
66
0
Order By: Relevance
“…Specifically, we recreate observations of gas velocity dispersion around edge-on discs. Wild et al (2014) proposed that heightened velocity dispersions perpendicular to the disc with respect to the velocity dispersion in the disc plane are evidence for bipolar outflows. We detect a signal in intermediate mass galaxies (10 ∼ < log M Halo / M ∼ < 11.5), though the ratio never exceeds two.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we recreate observations of gas velocity dispersion around edge-on discs. Wild et al (2014) proposed that heightened velocity dispersions perpendicular to the disc with respect to the velocity dispersion in the disc plane are evidence for bipolar outflows. We detect a signal in intermediate mass galaxies (10 ∼ < log M Halo / M ∼ < 11.5), though the ratio never exceeds two.…”
Section: Discussionmentioning
confidence: 99%
“…This galaxy was observed in the time allocated to the main survey since it seemed worthwhile to cover the full "mice" merger. These data have been published in (Wild et al 2014).…”
Section: Pairs and Interacting Galaxiesmentioning
confidence: 92%
“…The stellar dynamics together with detail analysis of the stellar populations revealed a tight relation between the initial mass function (IMF) and the local metallcity (Martín-Navarro et al 2015) and allowed us to dynamically constrain the shape of the IMF in early-type galaxies (Lyubenova et al 2016). vi) We explored in detail the impact of galaxy interactions on the enhancement of star-formation rates (SFR) and the ignition of galactic outflows (Wild et al 2014;Barrera-Ballesteros et al 2015b). vii) We studied the nature of the progenitors of SNe (Galbany et al 2014); viii) we explored star formation indicators for extended objects and the suitability of Hα as an SFR tracer (Catalán-Torrecilla et al 2015), as well as the spatially resolved SFR density across the Hubble sequence (González .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, IFS A&A 579, A45 (2015) observations of interacting galaxies are crucial for understanding whether the enhancement in the SFR is a global or a localized process. An example of the usefulness of such observations has been demonstrated by Wild et al (2014). From a detailed study of the Mice galaxies, they found that there is a moderate increment in the central SFR and no net enhancement in the global SFR.…”
Section: Introductionmentioning
confidence: 98%